2010
DOI: 10.1111/j.1472-765x.2010.02951.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of raw milk produced in Estonia

Abstract: Aims:  The microbial quality of farm bulk‐tank raw milk produced in Estonia during years 2004–2007 was investigated. Methods and Results:  Bulk‐tank milk samples were analysed for lactic acid bacteria count (LABC), psychrotrophic bacteria count (PBC), aerobic spore‐forming bacteria count (ASFBC), total bacterial counts using BactoScan and somatic cell count (SCC) using Fossomatic. Randomly selected psychrotrophic isolates were subjected to 16S–23S PCR‐ribotyping. LABC remained below 104 CFU ml−1 in most sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
2
13
0
1
Order By: Relevance
“…It seems that several efforts have been made to avoid biological contamination but the effort still to be more pronounced. The highest microbiological loads present in certain collecting points are certainly due to failure in respecting basic hygiene rules notably in pre-milking udder preparation and milk handlers, and also when storage equipment and transportation processes to the collect point by individual farms processes and [6][7][8][9][10][11][12][13][14][15]. This was confirmed by our observations made for some collecting points.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It seems that several efforts have been made to avoid biological contamination but the effort still to be more pronounced. The highest microbiological loads present in certain collecting points are certainly due to failure in respecting basic hygiene rules notably in pre-milking udder preparation and milk handlers, and also when storage equipment and transportation processes to the collect point by individual farms processes and [6][7][8][9][10][11][12][13][14][15]. This was confirmed by our observations made for some collecting points.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies in other areas in Morocco have not reported any contamination in collected raw milk [2] and [13]. The only exception was the report of Hadrya et al [15], but concerning not processed milk bought in specialized shops dedicated to raw products rather than raw milk produced in farms and destined to be processed industrially. Certainly, the temperature conservation procedures have not been respected.…”
Section: Discussionmentioning
confidence: 39%
“…In accordance with these findings, this study found the highest TBC during winter and spring (P>0.05). Stulova et al (21) reported that TBC was the highest in 131 farms in Estonia in June, and the lowest in November; and that TBC was >100.000 cfu/ml in 0.02% (3/131) of the farms. Similarly, in this study, TBC was at the lowest level in November, however highest levels were seen during winter.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, herdlevel somatic cell counts (SCCs), mastitis causing pathogens and their prevalence should be well known for detailed and comprehensive control program. There are some studies conducted in the USA (17), UK (6), Mexico (18), Canada (7,27), Norway (25), Finland (23), Estonia (9,36), Poland (34), Germany (39), Netherlands (32), and Denmark (12) to estimate herd and national-level mastitis pathogens, mastitis incidence and bulk tank milk somatic cell count. However, there are no studies for Northern Cyprus.…”
Section: Introductionmentioning
confidence: 99%